2018
DOI: 10.1051/0004-6361/201731783
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Lyman-α radiative transfer on large-scale clustering in the Illustris simulation

Abstract: Context. Lyman-α emitters (LAEs) are a promising probe of the large-scale structure at high redshift, z 2. In particular, the Hobby-Eberly Telescope Dark Energy Experiment aims at observing LAEs at 1.9 < z < 3.5 to measure the baryon acoustic oscillation (BAO) scale and the redshift-space distortion (RSD). However, it has been pointed out that the complicated radiative transfer (RT) of the resonant Lyman-α emission line generates an anisotropic selection bias in the LAE clustering on large scales, s 10 Mpc. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 63 publications
(52 reference statements)
0
30
0
Order By: Relevance
“…This holds despite the fact that we have no physical model for f (N HI , X) and only initial efforts to estimate it within cosmological simulations (e.g. McQuinn et al 2011;Rahmati et al 2013Rahmati et al , 2015Behrens et al 2018;Rogers et al 2018a,b).…”
Section: Constraints On the High Redshift Column Density Distributionmentioning
confidence: 98%
“…This holds despite the fact that we have no physical model for f (N HI , X) and only initial efforts to estimate it within cosmological simulations (e.g. McQuinn et al 2011;Rahmati et al 2013Rahmati et al , 2015Behrens et al 2018;Rogers et al 2018a,b).…”
Section: Constraints On the High Redshift Column Density Distributionmentioning
confidence: 98%
“…The non-gravitational bias in the large-scale clustering of LAEs by the Lyα RT (Zheng et al 2011;Behrens et al 2018) may complicate a cosmological analysis in HETDEX. In this paper, we showed that the impact of the large-scale gaseous environments around galaxies on Lyα line flux can be estimated from galaxy-Lyα forest cross-correlation data.…”
Section: Lyα Rt Effect On the Large-scale Lae Clusteringmentioning
confidence: 99%
“…Recently, Ref [70]. has found smaller selection effect at lower redshifts 2 < z < 6 from the radiative transfer simulation.…”
mentioning
confidence: 94%